Morris the moose - Wiseman, Bernard (New York : Harper & Row, 1989)
Determined to prove that the cow he meets is really a moose, Morris the moose enlists the help of a rather confused deer and horse.
Keywords: Moose -- Fiction; Animals -- Fiction; Humorous stories